A seca e as humanidades no processo de acesso à água: as barragens do Rio Salinas e o desenvolvimento regional - Magalhães, Maria Araci (2003)
This work is a synthesis of the dissertation about environments, socials, cultures, economicals impacts have ocurred in Salinas' region - MG, with the building of the dikes in the Caraíbas, Salinas Bananal rivers. Check the transformations have ocurred in the landscapes, in the life conditions of population included and its economical development.